Cultivation of native seaweed Gracilaria domingensis (Rhodophyta) in Southern Brazil - Salles,José Pedrassoli (2010)
The aim of this work was to study the cultivation of Gracilaria domingensis in a mussel farming urbanized area in Santa Catarina, Brazil. Relative growth rate was the parameter used to evaluate the cuttings attachment methods on the cultivation rope, cuttings density, cultivation period and cystocarpic versus unfertile thalli performance. The cultivation was feasible only when protected by net cages due to herbivory. The tie-tie attachment method presented the best results. No differences were observed when comparing the cuttings densities and reproductive phase. Future studies should evaluate the cost-effectiveness of producing the species in net cages and its potential as biofilter.